PENGARUH PROMOSI, KUALITAS LAYANAN, DAN PERSEPSI HARGA TERHADAPKEPUASAN KONSUMEN: (Studi Pada Pengguna Layanan Goride Gojek di Tangerang Selatan) - Cornelia Femitje Karundeng; Kartini Istikomah (Jurnal Ilmiah Manajemen dan Akuntansi, 2024)
High competition in the online transportation industry is marked by the increasing number of companies engaged in online transportation services, one of which is Gojek. This quantitative study aims to determine the effect received by consumer satisfaction with promotion, service quality and price perceptions on goride services in South Tangerang. Data was collected through distributing questionnaires. The sample used was 97 respondents. Non-probability sampling technique with purposive sampling method was used as the sample determination. The results showed that promotion, service quality, and price perception had a significant effect on customer satisfaction.